Effectiveness of Economic Token Techniques to Reduce Aggressive Behaviour in ADHD Children in SLBN Merangin - Witri Epilia; Marlina Marlina (Universitas Muhammadiyah Enrekang, 2022)
ADHD students are developmental disorders, attention disorders and concentration disorders, and cause excessive child behavior. Based on the problem above, students are very prominent in hitting, pushing, and pinching their friends. To reduce aggressive behavior the author uses the token economy technique so that students can reduce the aggressive behavior. This study aims to prove the effectiveness of the use of token economy techniques in reducing the physical aggressive behavior of ADHD children at SLBN Merangin. This type of research uses an experimental method using the Single Subject Research (SSR) research method, the design used is the Multiple-Baseline Across-Behaviors Design. Data collection techniques using observation and video recording. The data analysis technique uses analysis in conditions and analysis between conditions. In the form of graphic analysis, the results of economic research are effective in reducing aggressive behavior in ADHD children at SLBN Merangin.